Relating Sombor and Euler indices - Gutman, Ivan (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: The Euler-Sombor index (EU) is a new vertex-degree-based graph invariant, obtained by geometric consideration. It is closely related to the Sombor index (SO). The actual form of this relation is established. Methods: Combinatorial graph theory is applied. Results: The inequalities between EU and SO are established. Conclusion: The paper contributes to the theory of Sombor-index-like graph invariants.